2022
DOI: 10.3390/md20090567
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Metabolites from Marine-Derived Bacillus: A Comprehensive Review of Origins, Structures, and Bioactivities

Abstract: The marine is a highly complex ecosystem including various microorganisms. Bacillus species is a predominant microbialflora widely distributed in marine ecosystems. This review aims to provide a systematic summary of the newly reported metabolites produced by marine-derived Bacillus species over recent years covering the literature from 2014 to 2021. It describes the structural diversity and biological activities of the reported compounds. Herein, a total of 87 newly reported metabolites are included in this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…More extensive analyses, particularly in the fields of metabolomics, proteomics, and genomics, should be conducted with this strain to possibly detect metabolites and address this knowledge gap. B. amyloliquefaciens plantarum MLB3 was capable of producing the metabolites bacillaene, macrolactin W, surfactin B, surfactin C, and 7,13-epoxyl-macrolactin A under the conditions used in this study, all of which have proven antimicrobial activity [44,45]. For B. velezensis CL197, the following metabolites were identified: bacillaene, macrolactin A, macrolactin F, surfactin B, surfactin C, surfactin D, and 7,13-epoxyl-macrolactin A.…”
Section: Discussionmentioning
confidence: 84%
“…More extensive analyses, particularly in the fields of metabolomics, proteomics, and genomics, should be conducted with this strain to possibly detect metabolites and address this knowledge gap. B. amyloliquefaciens plantarum MLB3 was capable of producing the metabolites bacillaene, macrolactin W, surfactin B, surfactin C, and 7,13-epoxyl-macrolactin A under the conditions used in this study, all of which have proven antimicrobial activity [44,45]. For B. velezensis CL197, the following metabolites were identified: bacillaene, macrolactin A, macrolactin F, surfactin B, surfactin C, surfactin D, and 7,13-epoxyl-macrolactin A.…”
Section: Discussionmentioning
confidence: 84%
“…The non-ribosomal lipopeptides (NRPs) are cyclic lipopeptides (CLPs) and considered as common secondary metabolites. The CLPs are a class of metabolites with structural diversity produced by multifarious bacterial genera (Xiao et al 2022). They are built up by huge multimodular enzymes called non-ribosomal peptide synthetases.…”
Section: Detection Of Non-ribosomal Lipopeptides (Nrps) Genes In Used...mentioning
confidence: 99%
“…The iturin family sequences are composed of heptapeptides and a ß-amino fatty acid chain of 14-17 carbon atoms, which consists of bacillomycin D, F, L, Lc, iturin A, AL, C and mycosubtilin (Figure , 4). The plipastatin family comprise of ten amino acids and a ß-hydroxy fatty acid containing 14-18 carbon atoms (Figure 5) (Xiao et al 2022). Tapi et al (2010) reported that the use of degenerated primers is helpful in screening for various non-ribosomal genes which supported to detect a new non-ribosomal molecules and it facilitate the study and genetic potential knowledge of lipopeptide molecules biosynthesis.…”
Section: Detection Of Non-ribosomal Lipopeptides (Nrps) Genes In Used...mentioning
confidence: 99%
“…According to the data from the Natural Products Atlas 2.0, Bacillus species have been reported to produce at least 455 secondary metabolites, primarily including lipopeptides, polyketides, bacteriocin, lantibiotic, siderophore, and macrolactone ( van Santen et al, 2022 ; Xiao et al, 2022 ). These structurally diverse natural compounds exhibit a wide range of biological activities, including antimicrobial, antiviral, immunosuppressive, and antitumor activities ( Sansinenea and Ortiz, 2011 ; Xiao et al, 2022 ). Due to the extensive research on natural products from Bacillus strains, the continued exploration of novel natural products from Bacillus poses significant uncertainties and challenges.…”
Section: Introductionmentioning
confidence: 99%